Martir sebagai Persiapan memasuki Kesudahan segala Sesuatu (Eskatologi Kristen) - Buulolo, Oniaman; Harefa, Otniel Otieli; Jabes Pasaribu (STAK Reformed Remnant Internasional, 2025)
This article examines the significance of martyrdom in Christian theology as a means of preparing for the end of all things. The term of Martyr not only to illustrates how Christianity has often faced tragic rejection by the world, akin to the rejection experienced by Jesus, which has led to persecution and death a pattern mirrored by later Christian communities. In this writing, author employs a qualitative method with a narrative text approach for data analysis. The findings demonstrate that martyrdom is an intrinsic reality that is inextricably linked to the church, affirming a hope for future life amid the suffering that martyrdom entails. Consequently, martyrdom is framed as a vocational calling for the church in anticipation of the culmination of all things.